Implementation of Cyber-Link Marketing Model for MSME Partners of PT. Pertamina Hulu Rokan (PHR) - Hadi, Larbiel; Astari, Yanisha Dwi; Triyono, Wahyu (ABEC Indonesia, 2024)
This study aims to determine how the implementation of the Cyber-Link marketing model in MSMEs assistedby PT Pertamina Hulu Rokan (PHR). The analysis in this study used a quantitative descriptive method with data collectiontechniques using questionnaires and interviews with MSME actors. The population of this study are MSMEs assisted byPT Pertamina Hulu Rokan who are members of the Riau Cyber Community of Regional Featured Products (KaRiCePU)with a total sample of 63 MSMEs. Data analysis was carried out in four stages, namely editing, coding, tabulation, and dataanalysis. The results explained that the implementation of the Cyber-Link model succeeded in increasing product visibility,expanding market reach, and creating better interactions with consumers. However, challenges in technology adoption,including limited digital knowledge and internet access, were significant barriers. Recommendations from this studyinclude increasing digital training for MSME players and strengthening technology infrastructure to support thesustainability and growth of MSMEs in the digital era. This research is expected to provide insights for the developmentof more effective and innovative marketing strategies for MSMEs.